The Frequency of Substantial Salvageable Penumbra in Thrombectomy‐ineligible Patients with Acute Stroke. Issue 6 (16th July 2018) - Bahr Hosseini, Mersedeh; Woolf, Graham; Sharma, Latisha K.; Hinman, Jason D.; Rao, Neal M.; Yoo, Bryan; Jahan, Reza; Starkman, Sidney; Nour, May; Raychev, Radoslav; Liebeskind, David S.; Saver, Jeffrey L.
ABSTRACT: BACKGROUND AND PURPOSE: Endovascular therapy (ET) has become the standard of care for selected patients with acute ischemic stroke (AIS) due to large vessel occlusion (LVO). However, many LVO or medium vessel occlusion (MVO) patients are ineligible for ET, including some who harbor salvageable tissues. To develop complementary therapies for these patients, it is important to delineate their prevalence, clinical features, and outcomes. METHODS: In a prospectively maintained database, we reviewed consecutive AIS patients between December 2015 and September 2016. Based on the first multimodal computed tomography or magnetic resonance imaging, patients were categorized as having substantial penumbra if perfusion lesion volume ( T max >6 seconds) exceeded ischemic core volume (relative cerebral blood flow <30% on CT perfusion or apparent diffusion coefficient <620 on diffusion weighted image) by ≥20%. RESULTS: Among 174 consecutive AIS patients presenting within 24 hours of last known well time, 29 (17%) had LVO or MVO and substantial penumbra, but were deemed ET ineligible. Among these patients, mean age was 81 (±13), 45% were female, and median National Institute of Health Stroke Scale score was 11 (interquartile range [IQR]: 5–19). The most common reasons for not pursuing ET were: distal occlusion (28%), mild neurologic deficit (16%), and temporally advanced core injury (16%). Ischemic core volume was 20 mL (±31), penumbral volume was 54 mL (±63), and mismatch ratio median was 5.6 (IQR: 2‐infinite). Severe disability or death at discharge (modified Rankin scale: 4–6) occurred in 72% of the patients. CONCLUSION: Even in the modern stent retriever era, 1 in 6 AIS patients presents with substantial penumbra judged not appropriate for ET. This population may benefit from the development of alternative therapies, including collateral enhancement, neuroprotection, and thrombectomy devices deployable in distal arteries.